The Validity of Electronic Agreements in the Perspective of Indonesian Civil Law - Agnes Maria Janni Widyawati; Mig Irianto Legowo; Heri Purnomo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The advancement of digital technology has led to significant transformations across various sectors, including the legal field. One such change is the rise of electronic contracts (e-contracts), which allow business transactions to be conducted electronically without the need for the physical presence of the parties involved. E-contracts have become a vital alternative in many transactions within the digital age. This article aims to explore the validity of electronic contracts from the standpoint of civil law in Indonesia. It covers the legal framework governing electronic contracts, the requirements for their validity, and the challenges and issues encountered in their implementation in Indonesia. Through an analysis of existing legal provisions and a comparison with international practices, this article seeks to provide a clearer understanding of the legal standing of electronic contracts in Indonesia’s legal system.